Sinergi Badan Penanggulangan Bencana Daerah (BPBD) Kota Padang dengan Non Government Organization (NGO) Dalam Mengurangi Risiko Bencana Di Kota Padang - Nofia Sari Yanti; Zikri Alhadi (Jurusan Ilmu Administrasi Negara, 2019)
This research was motivated by the condition of Padang City which was at high risk of the earthquake and tsunami. Therefore an integrated and comprehensive disaster risk reduction effort is needed in order to minimize the adverse effects if an earthquake and tsunami occur at a time. The birth of Law No. 24 of 2007 changed the paradigm of disaster management, namely disaster management is the responsibility of the government, business and society. One of the bridges between the government and the community is NGOs. NGOs have a very important role in disaster management, especially in providing information from the public to the government. But in this case the synergy of Padang City BPBD and NGOs in reducing disaster risk is still lacking. This can be seen from efforts to reduce disaster risk dominated by NGOs. The method used in this research is descriptive qualitative method. The technique of collecting data uses observation, in-depth interviews, and documentation studies. Data analysis techniques using triangulation. The results showed that the Synergy of the Regional Disaster Management Agency (BPBD) of Padang City with Non Government Organizations (NGOs) in reducing disaster risk in the city of Padang had not been implemented well because cooperation between the BPBD of Padang City and NGOs was like conducting disaster socialization, dominated by NGO. Coordination between the Padang City BPBD and NGOs has also not been effective. This can be seen from several subindicators that have not been implemented properly, namely the continuity of coordination, clear formulation of authority and responsibility and effective communication.